Optimization of Assignment Problems using Hungarian Method at PT. Sicepat Express Ambon Branch (Location: Java City Kec. Ambon Bay) - Ardial Meik; Venn Yan Ishak Ilwaru; Monalisa E. Rijoly; Berny Pebo Tomasouw (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2022)
One of the special cases of problems in linear programming that is often faced by a company in allocating its employees according to their abilities is the assignment problem. The assignment problem can be solved using the Hungarian Method. In applying the Hungarian method, the number of employees assigned must be equal to the number of jobs to be completed. In this study, the Hugarian method was used to optimize the delivery time of goods from PT. SiCepat Express Ambon Branch – Java City. To solve the assignment problem at PT. SiCepat Express Ambon Branch – Java City, the required data includes employee names, destination locations, and delivery times. Before using the Hungarian method, the total delivery time of 7 employees at 10 destinations is 955 minutes. However, after using the Hungarian method, the total delivery time of 7 employees at 10 destination locations was 440 minutes. It can be seen that there are 515 minutes of time effisiency. We also Solved this assignment problem uses the QM For Windows Version 5.2 software and go the same amount of time, which is 440 minutes.